Teachers’ Perceptions of Communicative Approach in Teaching Speaking Skill Based on Emancipated Curriculum - Al Hakim, Abdul Malik; Rahayu Puji Haryanti; Rudi Hartono (English Education Journal, 2024)
This case study aims to know the teachers’ perception of the communicative approach and its implementation in teaching speaking skills based on an emancipated curriculum. The participants of this study consisted of three English teachers at three Islamic high schools in Demak Regency. Observations were conducted to evaluate the implementation of the communicative approach by analyzing teacher documents, specifically lesson plans. Also, questionnaires were distributed to investigate teacher perceptions regarding the communicative approach. It was analyzed using 16 principles of the communicative approach according to Larsen-Freeman's theory (2000). This study’s findings reveal that the three teachers have positive perception of implementing the communicative approach in teaching speaking skill based on the emancipated curriculum in Demak Regency. In implementing the communicative approach, guided by classroom observation and the teachers’ lesson plans, the teachers follow the sixteen principles of the communicative approach as outlined by Larsen-Freeman (2011). Teachers also use lesson plans using the principles of the communicative approach and carry out the teaching and learning process through the lesson plan. It can be concluded that the three teachers have a positive perception and implement the communicative approach based on the emancipated curriculum. This study also concludes that there is a relationship between the communicative approach and the emancipated curriculum. It can be seen in the similar principles and characteristics between the communicative approach and emancipated curriculum.